The influence of physical activity, specialized exercises and diet on pregnancy and delivery according to pregnant women attending a childbirth school - Spychalska, Julita (Journal of Education, Health and Sport, 2021)
The aim of the study was to show whether pregnant women are physically active and what their eating habits look like during pregnancy. To obtain a satisfactory answer, the questions were asked, the diagnostic survey method was used, and the technique was a questionnaire consisting of 18 questions. The first theoretical part shows the issues related to physical activity and the diet of a pregnant woman. The second-research part presents the entire research methodology - techniques, methods, hypotheses, theses, research tools and research area. In the final part, the results of the research, summary and conclusions are presented.